(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
We have carried out restoring of some Latvian alfalfa genetic resources from seeds of accessions that did not germinate in soil at all. Two of them were repatriated from the N. Vavilov All-Russian Institute of Plant Industry (multiplied more than 40 years ago) and three from the Research Institute of Agriculture (Latvia) (multiplied 15-20 years ago). For germination of old seeds we used early elaborated in vitro culture conditions. Germination rate ranged 2-60%, depending from the genotype and seeds storage conditions. Plantlets with well developed roots and 2-3 leaves were planted in the substrate in small pots and grown in a greenhouse about a month, then replanted in the soil in field conditions and grown till the maturity. Restored accessions are available now for evaluation and involving in the alfalfa breeding programs.